Podonomus fastigians Brundin 1966 (Chironomidae: Podonominae): Redescription of the adult male and female, the pupa, and description of the larva - Siri, Augusto (2009)
Fil: Siri, Augusto. Instituto de Limnología Dr. Raúl A. Ringuelet (ILPLA). Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina